Fibre morphological properties of Kelempayan (Neomalarckia cadamba sp.) wood / Siti Nadzirah Misfar and Jamaludin Kasim - Misfar, Siti Nadzirah; Kasim, Jamaludin (2011)
Fibre morphological properties are important factors that influence the strength properties of paper produced. The main objective of the study is to determine the fibre morphological properties (fibre length, fibre diameter and slenderness ratio or length to diameter ratio (L/D ratio)) of Kelempayan, with diameter of breast height ranging between 35cm and 41 cm. Three Kelempayan trees were harvested from UiTM Pahang forest and each of them was cut into three portions (bottom, middle and top). Samples were taken from each portion and along the distance of the stem (near pith, middle and near bark). The greatest fibre properties of Kelempayan according to the height level were found to be middle portion, followed by top and bottom portion. Along the distance, it was showed that fibre morphological properties were highest at near bark followed by middle and near pith except for fibre diameter. From the study. significant differences in fibre morphology of Kelempayan according to portion were found only in the fibre length and slenderness ratio (L/D ratio), while according to distance, all fibre properties were statistically significant .